2008
DOI: 10.1177/1534734608322099
|View full text |Cite
|
Sign up to set email alerts
|

Antimitotic Drug Injections and Radiotherapy: A Review of the Effectiveness of Treatment for Hypertrophic Scars and Keloids

Abstract: Scars are a common complication of surgery or burn wound management. Scars occur over the body, affecting people of both sexes and all ages. Scar therapy is a constant clinical challenge; antimitotic drugs and radiotherapy are used with varying degrees of success. This article examines the success of both these types of treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…The results of the present study are consistent with those of previous ones, one of which reported that the effectiveness rate of 5-FU injection alone was 62.5%, whereas the effectiveness of combined 5-FU and glucocorticoids was significantly higher at 92% (21,22). Intralesional 5-FU is generally well tolerated.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the present study are consistent with those of previous ones, one of which reported that the effectiveness rate of 5-FU injection alone was 62.5%, whereas the effectiveness of combined 5-FU and glucocorticoids was significantly higher at 92% (21,22). Intralesional 5-FU is generally well tolerated.…”
Section: Discussionsupporting
confidence: 83%
“…It disrupts the interconversion of uridine into thymidine through inhibiting thymidylate synthase. 20 , 21 It was originally used in the 1980’s as an adjuvant to glaucoma filtering surgery and in recent years for the treatment of a variety of malignancies. 2 , 20 Both in vitro and in vivo experiments have shown that 5-FU can inhibit fibroblast proliferation.…”
Section: -Fluorouracilmentioning
confidence: 99%
“…Colchicine is an antimitotic agent commonly used for cancer therapy because of its ability to inhibit collagen synthesis, cause microtubular disruption and increase the activity of collagenase. 21 , 41 Peacock et al studied the effects of colchicine in 10 patients with scars and reported positive results. However, because of its narrow therapeutic window its application is restricted.…”
Section: Potential Therapiesmentioning
confidence: 99%
“…Following this idea, probably the effect of the topical application of P144 may be enhanced in addition of a second agent, which can induce collagenolysis and cell apoptosis. Pulsed-dye laser [ 51 ], silicone-based products [ 52 ] and pressure dressings [ 53 ] can induce fibroblasts apoptosis and increase the collagen degradation. A combined drug therapy may yield greater efficacy and reduce side effects [ 54 ].…”
Section: Discussionmentioning
confidence: 99%